Factors Associated with Prevalence of Posttraumatic Stress Disorder among Nurses Working in COVID-19 Isolation Centres, Lagos, Nigeria - Tajudeen Olusegun Rasheed; Wasiu Adebowale Afolabi; Yisa Abiodun Bilawu; Kabiru Zubairu (Journal of Epidemiology and Public Health, 2023)
Background: Nurses are at increased risk of developing posttraumatic stress disorder (PTSD) due to response of the body and mind to a threatening working environment as they care for COVID-19 patients in isolation centres. This study determined the prevalence of PTSD and examined the associated factors among nurses working in COVID-19 isolation centres.Subjects dan Method: The study was a cross-sectional design. Purposive method was used to select two isolation centres, while 75 nurses who participated in the study were selected using total enumeration sampling technique. A structured questionnaire with validity and reliability established was used to collect data which were screened, collated and analyzed with SPSS 27. The Fisher’s Exact Test and Multivariate logistic regressions were the inferential statistics used to test the level of significant at p<0.050 and 95% confidence interval. The dependent variable of this study is posttraumatic stress disorder while the independent variables included socio-demographic characteristics of the participants, psychological and working conditions factors.Results: The mean age of the participants was (Mean=37.60; SD=10.20). Percentage of nurses having mild to severe PTSD was 27.8%. Duration stayed in COVID-19 isolation centres by nurses was significantly associated with the PTSD (p=0.003). The age, gender, marital status, and education level of the nurses were not statistically significant associated with the PTSD (p>0.05). Nurses who felt their life was under threat by working in COVID-19 isolation centres were 4.2 times more likely to develop PTSD compared to nurses who did not (OR=4.22, 95% CI=3.57 to 12.60, p=0.001).Conclusion: Nurses suffered PTSD due to psychological and physical exhaustion during the care of COVID-19 patients in isolation centres. Support program is recommended for the affected nurses to improve their quality of life. Keywords: COVID-19 isolation centres, nurses, PTSD, prevalence Correspondence: Tajudeen Olusegun Rasheed. Department of Health, Safety and Environment Studies, Training and Research Institute, Economic and Financial Crimes Commission, Academy, Karu, Abuja, Nigeria. Email: tajrash2005@gmail.com. Mobile: +2348038007373.